2019
DOI: 10.1523/eneuro.0110-18.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Restrained Dendritic Growth of Adult-Born Granule Cells Innervated by Transplanted Fetal GABAergic Interneurons in Mice with Temporal Lobe Epilepsy

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
(113 reference statements)
1
9
0
Order By: Relevance
“…Parvalbumin-positive interneurons associated in close proximity with the adult-born GCs (Gupta et al, 2019), form immature synaptic inputs onto proliferating newborn progeny and promote newborn neuronal progeny survival and development in the adult DG (Song et al, 2013), while suppressed PV-interneuron activity decreases the survival and maturation of newborn neurons (Song et al, 2013). In the present study, PV neurons were also spotted very close to NSCs.…”
Section: Discussionsupporting
confidence: 56%
“…Parvalbumin-positive interneurons associated in close proximity with the adult-born GCs (Gupta et al, 2019), form immature synaptic inputs onto proliferating newborn progeny and promote newborn neuronal progeny survival and development in the adult DG (Song et al, 2013), while suppressed PV-interneuron activity decreases the survival and maturation of newborn neurons (Song et al, 2013). In the present study, PV neurons were also spotted very close to NSCs.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, endogenous populations of hippocampal GABAergic interneurons promote survival of dentate GCs (Dieni et al, 2013), while endogenous subsets of PV-expressing hippocampal GABAergic interneurons specifically enhance survival of adult-born GCs (Song et al, 2013). We previously found that E13.5 MGE-derived transplants consist of approximately 37% PV+ GABAergic interneurons; many of the transplanted cells distribute throughout the molecular and GCL layers, where upon maturation, they form extensive inhibitory synaptic contacts to the dendrites of adult-born GCs (Hunt et al, 2013; Henderson et al, 2014; Gupta et al, 2019). Therefore, the transplanted cells may be responsible for increasing PV+ synaptic contacts with adult-born GCs, contributing to their survival and integration into synaptic networks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patch-clamp electrophysiological recordings in brain slices from mice with TLE showed increased spontaneous inhibitory postsynaptic currents in granule cells in slices with transplants (Henderson et al, 2014). The transplanted cells form extensive synaptic contacts associated with post-synaptic gephyrin puncta in the host brains and optogenetic stimulation of the transplanted cells induces strong inhibitory postsynaptic currents (Henderson et al, 2014; Gupta et al, 2019; Arshad et al, 2021). Despite mounting evidence that enhancing inhibitory synaptic transmission in the hippocampus or reducing adult neurogenesis are effective approaches for reducing seizures in rodent models of TLE, little is known about the underlying mechanisms for these therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, freshly obtained MGE cells may be more suitable for transplantation. Another possible structural mechanism for the anti-epileptic effect of MGE cells is increased GABAergic innervation by transplanted MGE progenitor cells, which may limit dendritic growth in adult hippocampal dentate granule cells ( Gupta et al, 2019 , Table 1 ). MGE progenitor cells from E13.5 GFP mice were transplanted into the hippocampus of mice 2 months after SE ( Casalia et al, 2017 , Table 1 ).…”
Section: Potential Of Medial Ganglionic Eminence Cell Transplantation...mentioning
confidence: 99%